The Thai Royalists’ Uses of Narratives in Their Defenses of a Politico-Moral Order - Unno, Anusorn (Journal of Social Sciences Naresuan University, 2025)
This article aims to examine the ways in which Thai royalists employed narratives in their defense of a politico-moral order against threats over the past two decades. It employed qualitative research methods primarily including in-depth interviews and document analysis, examining how Thai royalists constructed and told the narratives, what themes and plots of these narratives are, and the extent to which these narratives are convincing and able to defend the politico-moral order where righteousness is the main source of power. The article found that, considering themes and plots, Thai royalists constructed three narratives, including a righteous king under threats of a corrupt and disloyal politician, a sacred war between good and bad people, and informed adults instructing indoctrinated children. Drawing on religious concepts especially the Buddhist ones in their narrativization, the royalists achieved to defend the politico-moral order as their narratives were cited by the coups that ousted politicians considered a threat. Despite convincing at the initial stage, their narratives however became less convincing and thus less able to defend the politico-moral order, given changing socio-political circumstances and the discrepancy between them and the reality. The article argues that Thai royalists need to construct a new narrative or inevitably adopt a new politico-moral order so as to survive these challenges.